MEDIATION AS A METHOD FOR PREVENTING CONﬂ ICTS IN THE SPHERE OF PUBLIC ADMINISTRATION - Voloshyn, Volodimer; Mustafayeva, Urie S. (Public Administration and Regional Development, 2021)
The article presents an analysis of the social and legal nature of mediation and the possibilities of mediation as a way to prevent and resolve disputes (conﬂicts) in the public administration system. It is proved that the Ukrainian state is aware of the role of mediation in solving socially signiﬁ cant problems. The essence of mediation as a social phenomenon is that this method is focused on resolving disputes out of court, reaching consensus, agreeing to various conﬂ icting views, positions, and resolving controversial situations. It is a positive fact that this tool, as an alternative way of preventive prevention to prevent disputes (conﬂ icts), by taking into account the interests of each party and reaching a compromise solution, is in demand in society. The analysis of the legislation showed that considerable steps have already been taken on the path of introducing the practice of mediation, but this is not enough. It is necessary to adopt a special law on mediation, and amend the legislation. The adoption of the law will contribute to the professional organization and the introduction into wide practice at all levels of government and civil society of the institution of mediation, which will become an additional mechanism for resolving disputes, establishing communication and ﬁnding compromise and jointly produced consensus decisions between the authorities and society. The use of mediation in the public administration system will allow: to harmonize interests and maintain a balance of interests in any area of public relations; will strengthen the organizational potential of the subjects of management; strengthen coordination of actions and convergence of strategies of existing institutions of government and administration; will increase social stability in society and reduce conﬂ ict potential in society; will ensure the balance of state-management relations and the like. If we talk about the prospects for further research, then, in our opinion, they should relate to the study of the possibilities of using mediation in various ﬁ elds of activity and public life, including the study of the possibilities of using mediation as an alternative way to prevent disputes (conﬂ icts) in the processes of power and management activities.